Metal−dielectric parabolic antenna for directing single photons - Morozov,S; Gaio,M; Maier,S; Sapienza,R (Nano Letters, 2018)
Quantum emitters radiate light omni-directionally, making it hard to collect and use the generated photons. Here, we propose a three-dimensional metal–dielectric parabolic antenna surrounding an individual quantum dot as a source of collimated single photons, which can then be easily extracted and manipulated. Our fabrication method relies on a single optically induced polymerization step once the selected emitter has been localized by confocal microscopy. Compared to conventional nanoantennas, our geometry does not require near-field coupling, and it is, therefore, very robust against misalignment issues and minimally affected by absorption in the metal. The parabolic antenna provides one of the largest reported experimental directivities (D = 106) and the lowest beam divergences (Θ1/2 = 13.5°) and a broadband operation over all of the visible and near-infrared range together with extraction efficiency of more than 96%, offering a practical advantage for quantum technological applications.